THE EFFECT OF BUTEYKO BREATHING AND ASTHMA EXERCISE ON ASTHMA SYMPTOMS AMONG PATIENTS WITH ASTHMA - erik kusuma (The Indonesian Journal of Health Science, 2021)
Asthma is a chronic inﬂammatory disease of the airways and is on the increasing trend owing to air pollution and urbanization. The use of alternative ways of treatment that are as efﬁcacious as the standard treatment is needed. This study aims to assess the effect of buteyko breathing and asthma exercise on reducing asthma symptoms. A quantitative approach with true experimental design was adopted for the study. Simple random sampling technique was adopted to select 18 samples for the study, 9 samples each for the experimental (buteyko) and control (asthma exercise) groups. The duration of the study was 2 weeks. The effects were assessed using the weekly asthma symptom questionnaire. The dependent T-test was used to see the difference in asthma symptom scores at the initial and final visit of the 2nd week in both groups. Independent T-test was used to determine the difference in the decrease of asthma symptom scores between two groups after 2 weeks of action. The study showed that there were a significant difference in asthma symptom scores at the initial and final visit of the 2nd week in both groups (p 0.00 0.05). However, in experimental group the decrease of asthma symptom scores were more significant (eta squared 0.99 compared to 0.94), so it was concluded that the Buteyko breathing was more effective than asthma exercise in reducing asthma symptoms (p 0.000 0.05). Buteyko breathing was found to be more significantly effective on reducing asthma symptoms among patients with asthma.